The impact of the minimum wage on poverty and industrial relations in the hospitality industry in Grahamstown, South Africa - Maqubela, Zikisa (Rhodes University, Faculty of Humanities, Department of Sociology, 2020)
This dissertation endeavours to unpack and understand the impact of the minimum wage on the hospitality industry with a specific focus on Grahamstown. The areas of impact that are of immediate interest were the impact on poverty and industrial relations. In operationalising this research, a qualitative research approach was adopted. The overall design of the study was a case study in a bid to ensure deeper insights may be extracted from semi-structured interviews that were then thematically analysed. Theoretically, the study was guided by the understanding of citizenship as articulated by Mamdani as well as Keynesian theory. The central theme when exploring the minimum wage in relation to poverty is that the minimum wage that is currently paid is enough to aid workers and their families in escaping abject poverty, however, it does not go far enough to further ensure that they totally escape poverty as measured by the Upper Bound Poverty Line. The inadequacy of the minimum wage in ensuring that people are pushed out of poverty would then mean that their claims to citizenship are compromised and the quality of life they can access is often below what would be readily accepted of a citizen of South Africa. Lifestyle entrepreneurs offer an alternative approach to doing business that can see higher pay as further entrench claims to citizenship. The central case around industrial relations is that the impact of the minimum wage is indeterminate for two reasons. Broadly speaking, the impact would need to be reviewed at a macro-level and not simply within the impacted sectors. This is the various interconnected value chains that could feel indirect impacts at the initiation of a minimum wage. Further, the impact such changes has to individual firms is also indeterminate as employers have a range of choices that they can adopt in absorbing the impact of a minimum wage, which may include simply increasing the price the end consumer pays or retrenching some staff members. However, the choice that employers would make in this context is not predetermined but rather would vary between firms due to the very specifics of each firm.
Keywords: Hospitality industry -- South Africa -- Grahamstown; Minimum wage -- South Africa -- Grahamstown; Poverty -- South Africa -- Grahamstown; Wages -- South Africa -- Grahamstown; Service industries workers -- South Africa -- Grahamstown; Industrial relations -- South Africa -- Grahamstown